Evaluation of Telekom Malaysia Bhd’s financial performance for year 2005-2009 / Nur Jihan Md Johan - Md Johan, Nur Jihan (Faculty of Business and Management, 2011)
In study of financial statement analysis, there are several types of financial ratios. The ratios are capital structure and solvency ratios, profitability ratios, liquidity ratios, activity ratios, and market ratios. Therefore, in researcher study, researcher will use two types of ratios that is capital structure and solvency ratios and also profitability ratios. Under capital structure and solvency ratios, researcher will use the debt to equity ratios method. Then, under profitability ratios researcher will use return on assets and return on equity ratios method. These methods researcher use because researcher wants to investigate on this Telekom Malaysia Bhd. Financial ratios, These ratios also Telekom Malaysia Bhd had used as their one of measurement financial performance in annual report. (Annual report 2005-2009) Moreover, in this study, researcher wants to analyse the trend of Telekom Malaysia Bhd financial performance. This case study was conducted because researcher found that their Debt to Equity ratio (Capital structure and solvency) is not maintained and increases from year 2007 until 2009. Then, in Return on Assets ratios (Profitability ratios), researcher found that the percentage are getting lower from year 2007 until year 2009. Next, in their Return on Equity ratios (Profitability ratio), researcher found that percentage of return is unstable. From year 2005 until year 2007 the return is high, however, in year 2007 until year 2008, the return is decrease and in year 2009 the return is increase back but in little percentage. In brief, this situation makes researcher triggers to reveal and argue with what the researcher had study in financial analysis and what this company had practice. Based on Telekom Debt to Equity ratio (Capital structure and solvency), it shows that in year 2005 until 2007 the ratio is maintain, however, in year 2007 till year 2009 their debt equity ratios is increase up to 1.0. The higher the proportion of debt, the larger the fixed charges interest and debt repayment and the greater likelihood of insolvency during period earnings. (Subramanyam and Wild 2009) In same study also said that, a ratio in excess of 1:1 indicates greater long term debt financing compared to equity capital. If the ratio is less meaning the company is able to meet with their debt obligation. In theory had said that the lower Debt to Equity ratio (Capital structure and solvency) is better for a company. This is according to Gitman and Joehnk (2008), a low or declining debt equity ratio is preferable, as that would suggest the firm has a more reasonable debt load and therefore less exposure to financial risk. In addition, this debt to equity ratio (Capital structure and solvency) is related with Telekom asset management and others on going operations activities made by this company. When researcher studies about this company, researcher believes that this Telekom Malaysia Bhd has the ability to increase more their debt ratio. This is because this company always develop new product and always put huge number of capital expenditure for their new development.